The Impact of Income on the Division in Domestic Labor: The Case Study in Rural Vietnam - Minh Le, Phuong Nu (Asian Development Policy Review, 2022)
The imbalance in the distribution of responsibilities for unpaid work has profoundly affected women’s’ empowerment and full participation in economic and social activities. The study surveyed more than 150 households in one rural area in one Vietnamese province. This study's result in the central rural area did not improve Vietnamese domestic labor division compared to previous studies. The daily time taken up doing housework strongly correlates with gender, and the t-Test is statistically significant differences in the mean by gender. Wives earn additional money, and then spend less time on housework; nonetheless, the wife's minimum threshold for housework time is much higher than her husband's maximum threshold. Unlike the time devoted to housework, how much income contributes to the household does not affect childcare time. Except for the gender factor, the importance and extent of factors affecting housework and childcare differed markedly. Peculiarly, the unemployment of husbands is not a normal situation in Vietnamese families, so the assumption of exchange theory is not satisfied, though the wife is almost unable to negotiate with the unemployed husband.